Business doing good engaging women and elevating communities - Deer, Shannon, 1981- (Rowman & Littlefield Publishers, 2021)
"Business Doing Good outlines six principles businesses can implement to effectively hire women who have experienced incarceration, poverty, addiction, and/or engagement in the sex trade. While making a difference to both women and communities, businesses will benefit from the many unique skills and perspectives these resilient women bring to work"--